Thermal stability of Mg2Si0.4Sn0.6 in inert gases and atomic-layer-deposited Al2O3 thin film as a protective coating. Issue 45 (3rd November 2016) - Zhang, Libin; Chen, Xi; Tang, Yinglu; Shi, Li; Snyder, G. Jeffrey; Goodenough, John B.; Zhou, Jianshi
Abstract : The structure and thermoelectric properties of Mg2 Si0.4 Sn0.6 are unstable above 700 K. We demonstrated atomic-layer-deposited Al2 O3 as a protective coating to address this problem. Abstract : Mg2 Si1− x Sn x solid solutions are promising thermoelectric materials to be applied in vehicle waste-heat recovery. Their thermal stability issue, however, needs to be addressed before the materials can be applied in practical thermoelectric devices. In this work, we studied the crystal structure and chemical composition of Mg2 Si1− x Sn x in inert gas atmosphere up to 823 K. We found that the sample was oxidized even in high-purity inert gases. Although no obvious structural change has been found in the slightly oxidized sample, carrier concentration decreased significantly since oxidation creates Mg vacancies in the lattice. We demonstrated that an atomic-layer deposited Al2 O3 coating can effectively protect Mg2 Si1− x Sn x from oxidation in inert gases and even in air. In addition, this Al2 O3 thin film also provides in situ protection to the Sb-doped Mg2 Si1− x Sn x samples during the laser-flash measurement and therefore eliminates the measurement error that occurs in uncoated samples as a result of sample oxidation and graphite exfoliation issues.